Health behavior of working-aged Finns predicts self-reported life satisfaction in a population-based 9-years follow-up - Stenlund Säde; Koivumaa-Honkanen Heli; Sillanmäki Lauri; Lagström Hanna; Rautava Päivi; Suominen Sakari (BMC, 2025)
Background: Previous studies have shown positive association between health behavior and life satisfaction, but the studies have mostly been cross-sectional, had follow-up times up to 5 years or focused on only one health behavior domain. The aim of the study was to explore how principal health behavior domains predict life satisfaction as a composite score in a previously unexplored longitudinal setting.
Methods: The present study tested whether a health behavior sum score (range 0-4) comprising of dietary habits, smoking, alcohol consumption, and physical activity predicted subsequent composite score of life satisfaction (range 4-20). Data included responses from 11,000 working-age Finns who participated in the Health and Social Support (HeSSup) prospective population-based postal survey.
Results: Protective health behavior in 2003 predicted (p < .001) better life satisfaction 9 years later when sex, age, education, major diseases, and baseline life satisfaction were controlled for. The beta in the linear regression model was - 0.24 (p < .001) corresponding to a difference of 0.96 points in life satisfaction between individuals having the best and worst health behavior.
Conclusion: Good health behavior has a long-term beneficial impact on subsequent life satisfaction. This knowledge could strengthen the motivation for improvement of health behavior particularly on an individual level but also on a policy level.